2019
DOI: 10.1111/ajo.12987
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, mental health and ‘wellness’ in obstetricians and gynaecologists: Why these issues should matter to our patients – and our profession

Abstract: Healthy doctors understand us better, make good decisions, and offer us the best chance of good health. 1 In October of 2017, the World Medical Association updated and amended its 'physician's pledge' -the Declaration of Geneva 2 -to include a new affirmation: 'I will attend to my own health, well-being, and abilities in order to provide care of the highest standard.' This was a major addition to a time-honoured set of principles, significant enough to prompt worldwide attention in both the medical and lay pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Stressors such as recurrent and prolonged selfisolation, taking time off as a carer, having family members affected, delayed milestone professional exams, a drastic reduction in operative workload and the uncertainty about training progression are some of many reasons leading to prolonged mental health sequalae. Failure to ensure HCP's well-being can lead to burnout, poor patient care (Robson and Cukierman, 2019), more medical errors and higher absenteeism (Shanafelt et al, 2010). Furthermore, O&G historically is a profession with a high burnout rate, and this is likely to worsen due to COVID-19 pandemic (Bourne et al, 2019;RCOG 2020a).…”
Section: Table II Trainee Responses Regarding Wellbeing Training and ...mentioning
confidence: 99%
“…Stressors such as recurrent and prolonged selfisolation, taking time off as a carer, having family members affected, delayed milestone professional exams, a drastic reduction in operative workload and the uncertainty about training progression are some of many reasons leading to prolonged mental health sequalae. Failure to ensure HCP's well-being can lead to burnout, poor patient care (Robson and Cukierman, 2019), more medical errors and higher absenteeism (Shanafelt et al, 2010). Furthermore, O&G historically is a profession with a high burnout rate, and this is likely to worsen due to COVID-19 pandemic (Bourne et al, 2019;RCOG 2020a).…”
Section: Table II Trainee Responses Regarding Wellbeing Training and ...mentioning
confidence: 99%
“…This can still be conducted by training supervisors over videoconferencing to identify trainees exposed to potentially traumatic situations caused either by this pandemic or through the course of routine work and dissect these to increase awareness of limitations, identify abnormal stress responses and come up with strategies to overcome them. This aims to ‘normalise vulnerability’ and enable learning unique lessons during this pandemic 13 …”
Section: Training Program Levelmentioning
confidence: 99%
“…9 showed that HCPs during pandemics suffered higher levels of 10,11 have caused uneven clinical experience, case log deficits, and uncertainty regarding training progression. 12 Failure to ensure HCPs' well-being can lead to burnout, poorer patient care, 13 more medical errors, 14 and higher absenteeism. 8,15 We describe our efforts to maintain trainees' mental well-being in our university-affiliated teaching hospital in Singapore.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5] This prevalence has been attributed in part to the nature of obstetric care, which requires immediate attention to clinical emergencies, prolonged and complex surgical procedures, litigation threat and lengthy shifts. [6][7] Performance anxiety also plays a role, with junior doctors expressing fears regarding public criticism as a contributory factor. 8 Nowhere is the junior doctor more likely to face such criticism than in the setting of acute service clinical handover.…”
Section: Introductionmentioning
confidence: 99%